A Phase-Field Model Coupled with Lattice Kinetics Solver for Modeling Crystal Growth in Furnaces (Communications in Computational Physics, 2014)
In this study, we present a new numerical model for crystal growth in avertical solidification system. This model takes into account the buoyancy inducedconvective flow and its effect on the crystal growth process. The evolution of the crystal growth interface is simulated using the phase-field method. A semi-implicit latticekinetics solver based on the Boltzmann equation is employed to model the unsteadyincompressible flow. This model is used to investigate the effect of furnace operationalconditions on crystal growth interface profiles and growth velocities. For a simplecase of macroscopic radial growth, the phase-field model is validated against an analytical solution. The numerical simulations reveal that for a certain set of temperatureboundary conditions, the heat transport in the melt near the phase interface is diffusiondominant and advection is suppressed.